2007
DOI: 10.1159/000102540
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of Vitamin D Receptor Distribution in Goat Intestines

Abstract: Vitamin D (VD) plays an important role in calcium homeostasis. 1,25-Dihydroxycholecalciferol or calcitriol modulates gene transcription via nuclear VD receptors (VDR). In the intestines, VD promotes calcium resorption via VDR. VDR has not been systematically assessed within the intestine in any species. We therefore present a semiquantitative immunohistochemical study of the distribution patterns of VDR in goat intestines. Intestinal tissue probes were collected from 5 lambs and 5 non-lactating non-pregnant da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…The results of the present immunohistochemical study in growing goats demonstrated that VDR are present in all intestinal segments, as was also shown in earlier studies (Boos et al, 2007;Liesegang et al, 2008;Riner et al, 2008). The observed VDR-immunoreactivities were prominent in duodenal mucosa, lower in jejunum and colon, further declined in ileum and were lowest in caecum.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present immunohistochemical study in growing goats demonstrated that VDR are present in all intestinal segments, as was also shown in earlier studies (Boos et al, 2007;Liesegang et al, 2008;Riner et al, 2008). The observed VDR-immunoreactivities were prominent in duodenal mucosa, lower in jejunum and colon, further declined in ileum and were lowest in caecum.…”
Section: Discussionsupporting
confidence: 91%
“…In every tissue specimen, . The semiquantitative evaluation of histochemical reactions for VDR was performed as described previously, i.e., an immunoreactive score (IRS) was calculated for the colored intensity (CI) using this formula (Boos et al, 2007;Liesegang et al, 2008): VDR-IRS = 0 x n(CI 0 ) + 0.25 x n(CI 0,5 ) + 1 x n(CI 1 ) + 4 x n(CI 2 ) + 9 x n(CI 3 ).…”
mentioning
confidence: 99%
“…Semiquantitative immunocytochemical studies with antibodies to vitamin D receptor noted differences in vitamin D receptor staining in goat intestine in segment-and location-specific patterns (49). Changes of enterocyte expression of receptor and function are likely to occur during their migration from crypts to the tip of villi and to hormonal effects during sexual maturation as observed in connection to altered calcium transport in chickens (50).…”
Section: Small Intestinementioning
confidence: 99%
“…There was only weak VDR expression in the colon in healthy dogs, a finding which is different to people and other species. 39,51 In human ulcerative colitis and in mouse models of colitis, VDR expression is negatively correlated with colonic inflammation.…”
Section: Discussionmentioning
confidence: 99%